2021
DOI: 10.3390/antibiotics10020211
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Effect of Cold Atmospheric Plasma against Dental Pathogens—A Systematic Review of In-Vitro Studies

Abstract: Interest in the application of cold atmospheric plasma (CAP) in the medical field has been increasing. Indications in dentistry are surface modifications and antimicrobial interventions. The antimicrobial effect of CAP is mainly attributed to the generation of reactive oxygen and reactive nitrogen species. The aim of this article is to systematically review the available evidence from in-vitro studies on the antimicrobial effect of CAP on dental pathogens. A database search was performed (PubMed, Embase, Scopu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 98 publications
(151 reference statements)
2
36
0
Order By: Relevance
“…RONS cause photodesorption or etching of the cell wall, peroxidation of lipids and ergosterol, the latter being a critical sterol of the cell membrane [57]. This leads to an increase in membrane permeability favoring leakage of cytoplasm and intracellular components, and ultimately to lethal cellular damage [40,53,58,59]. Our SEM images highlighted the rupture of the cell membrane and the leakage of intracellular components after a 120-min O 2 NTP, which is in accordance with the previous hypotheses.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…RONS cause photodesorption or etching of the cell wall, peroxidation of lipids and ergosterol, the latter being a critical sterol of the cell membrane [57]. This leads to an increase in membrane permeability favoring leakage of cytoplasm and intracellular components, and ultimately to lethal cellular damage [40,53,58,59]. Our SEM images highlighted the rupture of the cell membrane and the leakage of intracellular components after a 120-min O 2 NTP, which is in accordance with the previous hypotheses.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, destroying those clusters was more difficult due to their thickness and the presence of an extracellular matrix. Hence, the deeper yeast layers were better protected from NTP [37,40,61]. According to many authors [38,40,53], increasing the treatment time or producing intracellular ROS in biofilm [62] would favor the destructuration of those clusters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, periodontal disease treatment was primarily aimed at controlling accumulation of the microbial dental plaque, which has an important role in the onset and progression of periodontal disease. NTAP is being currently investigated as an antiseptic, and several studies have revealed the antibacterial effect both in vivo and in vitro [54]. In addition, the most obvious advantage that is accepted in this regard is that plasma achieves this effect without damaging human cells [55].…”
Section: Discussionmentioning
confidence: 99%